Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar IPA Materi Kelainan Otot Manusia pada Peserta didik Kelas V Sekolah Dasar - Purwanti, Yanti (Universitas Sebelas Maret, 2020)
The application of innovative learning models can affect student learning outcomes. Based on observations at SD N Laren 04, the conditions include: students tend to be passive in learning, the learning method used is still monotonous, only lectures, question and answer and have not involved students to make discoveries independently or in groups. This study aims to improve science learning outcomes for muscle disorders in humans with the research subjects being all students of class V SD N Laren 04, totaling 12 students. This research is a classroom action research conducted in two cycles. Each cycle in this study went through the stages of planning, implementation, observation, and reflection. Data collection techniques used are observation and field notes. The results showed that the results of observations in the first cycle of 64% and in the second cycle increased to 88%. Based on the results of the study, it can be concluded that the application of the Problem Based Learning model can improve science learning outcomes for human muscle disorders in class V SD N Laren 04.